Ultracompact vanadium dioxide dual-mode plasmonic waveguide electroabsorption modulator - Bai, Ping (2016)
Subwavelength modulators play an indispensable role in integrated photonic-electronic circuits. Due to weak light-matter interactions, it is always a challenge to develop a modulator with a nanometer scale footprint, low switching energy, low insertion loss and large modulation depth. In this paper, we propose the design of a vanadium dioxide dual-mode plasmonic waveguide electroabsorption modulator using a metal-insulator-VO2-insulator-metal (MIVIM) waveguide platform. By varying the index of vanadium dioxide, the modulator can route plasmonic waves through the low-loss dielectric insulator layer during the “on” state and high-loss VO2 layer during the “off” state, thereby significantly reducing the insertion loss while maintaining a large modulation depth. This ultracompact waveguide modulator, for example, can achieve a large modulation depth of ~10 dB with an active size of only 200×50×220 nm3 (or ~λ3/1700), requiring a drive-voltage of ~4.6 V. This high performance plasmonic modulator could potentially be one of the keys towards fully-integrated plasmonic nanocircuits in the next-generation chip technology.